DIGITAL DETOX POLICY AS A STRATEGIC TOOL TO REDUCE BURNOUT AND INCREASE PRODUCTIVITY IN MULTINATIONAL COMPANIES - Tiara Nirmala; Nasrullah Djamil; IGP Ratih Andaningsih (Maneggio, 2025)
This study aims to analyze digital detox policy as a managerial strategy to reduce burnout and enhance employee productivity in multinational corporations. The phenomenon of digital overload caused by constant connectivity has created significant psychological pressure and emotional exhaustion within global work environments. Adopting a descriptive–qualitative approach with a juridical–managerial framework, this study integrates Strategic Human Resource Management (SHRM), Self-Determination Theory (SDT), and the Job Demands–Resources (JD-R) model. Data were collected through literature reviews and semi-structured interviews with 12 HR managers from four multinational companies operating in Southeast Asia and Europe. Findings reveal that strategically integrated digital detox policies including restricted digital access hours, digital mindfulness training, and right to disconnect initiatives, reduced burnout levels by up to 25% and improved work engagement and overall productivity by 12% on average. The results highlight that digital detox should be viewed not merely as a wellness initiative but as a strategic instrument that strengthens competitiveness and human-centered sustainability within global organizations. The study recommends stronger top management commitment and cross-functional collaboration to ensure consistent and culturally adaptive implementation of digital detox policies across multinational contexts.